Randomized controlled trial on lifestyle - (:unkn) unknown (SAGE PUBLICATIONS INC, 2006)
The authors examined the effects of a comprehensive lifestyle modification intervention on blood pressure (BP) and other cardiovascular risk factors in hypertensive patients. A total of 70 participants were randomly placed into either a lifestyle intervention or a control group. Four education classes and individual counseling sessions were held for the intervention group. Participants in the control group were provided with routine outpatient services and were asked to maintain their usual lifestyle. Data were gathered at baseline and at the end of 6 months. At the end of 6 months, BP, body weight, body mass index, waist circumference, and fasting lipids, apart from high-density lipoprotein cholesterol, significantly declined in the intervention group. Health-promoting lifestyle scores of the intervention group had increased significantly compared to those of the control group. In conclusion, the results demonstrate the feasibility of comprehensive lifestyle modification and show its beneficial effects.
Keywords: hypertension; lifestyle modification; patient education; cardiac; risk factors; QUALITY-OF-LIFE; BLOOD-PRESSURE; WEIGHT-LOSS; AEROBIC EXERCISE; SUBGROUP ANALYSIS; SODIUM REDUCTION; DIETARY-SODIUM; PUBLIC-HEALTH; HYPERTENSION; EDUCATION